ASSOCIATION OF HIGH LIPOPROTEIN(a) LEVELS WITH CORONARY ARTERY PATENCY DURING THE FIRST YEAR AFTER PERCUTANEOUS CORONARY INTERVENTIONS - M. V. Ezhov; M. S. Safarova; Yu. G. Matchin; D. I. Soboleva; O. I. Afanasyeva; S. N. Pokrovsky (Klinicist)
Objective: to study an association of high lipoprotein(a) [Lp(a)] levels with the development of restenosis and the progression of coronaryatherosclerosis after percutaneous coronary interventions (PCI) in patients with chronic coronary heart disease (CHD).Subjects and methods. From 502 enrolled patients (mean age 54.7 ± 8.9 years), 92 underwent routine percutaneous transluminal coronary angioplasty (PTCA), 270 had PTCA with the bare metal stent (BMS) being implantation, 140 had PTCA using drug-eluting stents (DES). Functionalclasses III and IV angina have been registered in 337 (67 %) patients; history of one myocardial infarction (MI) was noted in 234 (47 %) cases, 171 (34 %) had experienced 2 or more MIs. Blood samples for lipid and Lp(a) measurements were taken in all the patients. Restenosis was defined as at least 50 % lumen narrowing of the coronary artery segment after angioplasty. Coronary atherosclerosis progression was established in cases of the new occlusion occurring, as well as identifying a 10 % decrease in lumen diameter in comparison with baseline angiograms.Results. Repeated coronary angiography revealed the signs of restenosis in 103 of 243 patients. Dividing patients into 3 groups according to the type of intervention demonstrated that the level of Lp(a) (median 25–75 % quartiles) was significantly higher in the restenosis group after implantation of BMS (33; 11–62 and 16; 6–39 mg/dl, respectively; p = 0.014) versus those who had undergone DES implantation (23; 10–30 and 20; 6–60 mg/dl; p = 0.7) or balloon angioplasty (17; 4–48 and 9; 4–36 mg/dl; p = 0.3). Patients with progression of coronary atherosclerosis had difference only in Lp(a) levels compared to the group without progression (36; 13–62 versus 12; 4–26 mg/dl, p < 0,001.Conclusion. During the first year after elective PCI Lp(a) concentration determined the severity of coronary atherosclerosis in non-culprit lesionsand associated with the risk of in-stent restenosis after BMS, independly of conventional risk factors.